Indirect relationship of attachment, immediacy, interpersonal needs and interpersonal attraction between emotional intelligence and life satisfaction: an empirical study of Malaysian undergraduates - Ramachandran, Kunnasunthary S.; Hamsan, Hanina Halimatusaadiah; Mohd Khir, Azlina (Human Resource Management Academic Research Society, 2020)
Life satisfaction is a global evaluation can be determined by a strong capability of thoughts and feeling called emotional intelligence. At the same time, these two elements indirectly effect by certain psychosocial attributes such as attachment relationship of lecturers, attachment relationship of peers, immediacy behaviour of lecturers, interpersonal needs and interpersonal attraction of peers. Therefore, aim of this study proposed that determine the indirect relationship of attachment, immediacy, interpersonal needs and interpersonal attraction between emotional intelligence and life satisfaction among 600 undergraduate students in Klang Valley area. The two theories applied in this study are, PERMA model and Emotional Intelligence The results support the hypothesis of the study and revealed that attachment relationship of lecturer's, immediacy behaviour of lecturer's and interpersonal needs of students significantly played a mediator role based on Hayes Mediation Analysis Bootstrapping. It means there was an indirect and direct relationship between variables. Students, who had positive psychosocial attribution, had high level of emotional intelligence and life satisfaction.